KSDC as an insurance consultant for Kedah Darul Aman state government – "Trans Eastern Kedah Interland Highway project from Durian Burung to Kupang, Kedah". Case study: KSDC Insurance Brokers Sdn Bhd / Nurul Atiqah Marzuki - Marzuki, Nurul Atiqah (2010)
Insurance Brokers Company involves the process of handling the insurance on behalf of the insured or proposer with the insurance company. Insurance Brokers is an independent agent who represents the buyer, rather than the insurer or insurance company, they tries to find the buyer the best policy by comparison shopping. This study is about implementation of brokerage process in state government project by KSDC Insurance Brokers Sdn Bhd. It consists of introduction which will briefly explain on the company background, issue and elements of study and also the purpose of study. The study will be focus on practice, procedure and discuss more on the way of brokerage process and management. It will briefly discuss on the way Broker Company appointed the insurer, the role and how they manage to extend the coverage on the project. The information gathering will be based on an extensive research of the relevant journal, articles, websites and related documents about company practice and brokerage process. The conclusion of this study shall be based on the outcome from the findings. Through the research, it shows that there are little different between the fact and company practice.